SOME FACTORS RELATED TO THE SELF-CARE PRACTICES OF OUTPATIENTS WITH HEART FAILURE AT THE CARDIOLOGY DEPARTMENT, VINMEC TIMES CITY INTERNATIONAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: Identify some factors related to the self-care practices of outpatients with heart failure at the Cardiology Department, Vinmec Times City International Hospital in 2024. Methods: Analytical cross-sectional study.Results: The equation predicts the "Self-care Maintenance" score: Y = 35.957 + 3.183 × Education Level (1 = Below High School; 2 = High School or Above) + 1.478 × General Knowledge Score (points) + ε (residual) with an adjusted R2 of 0.344. The equation predicts the "Self-care Management" score: Y = 80.464 − 0.598 × Age (years) + 5.449 × Education Level (1 = Below High School ; 2 = High School or Above) + ε (residual) with an adjusted R2 of 0.413. The equation predicts the "Self-care Confidence" score: Y = 89.085 − 0.865 × Age (years) + 9.290 × Family History (1 = Yes, 2 = No) + ε (residual) with an adjusted R2 of 0.443.Conclusion: The study indicates some independent variables that can predict the "Self-Care Maintenance" score, "Self-Care Management" score, and "Self-Care Confidence" score for outpatients with heart failure.
Keywords: Related factors; practices; self-care; heart failure; outpatient treatment